Low tumor infiltrating mast cell density confers prognostic benefit and reflects immunoactivation in colorectal cancer. Issue 9 (7th August 2018) - Mao, Yihao; Feng, Qingyang; Zheng, Peng; Yang, Liangliang; Zhu, Dexiang; Chang, Wenju; Ji, Meiling; He, Guodong; Xu, Jianmin
Abstract : The role of mast cells (MCs) in colorectal cancer (CRC) progression was controversial. Thus, our study was designed to evaluate the prognostic value of MCs as well as their correlation with immune microenvironment. A retrospective cohort of CRC patients of stages I–IV was enrolled in our study. Consecutive patients (854) were divided into training set (427 patients) and validation set (427 patients) randomly. The findings were further validated in a GEO cohort, GSE39582 (556 patients). The mast cell density (MCD) was measured by immunohistochemical staining of tryptase or by CIBERSORT algorithm. Low MCD predicted prolonged overall survival (OS) in training and validation set. Moreover, MCD was identified as an independent prognostic indicator in both sets. Better stratification for CRC prognosis can be achieved by building a MCD based nomogram. The prognostic role of MCD was further validated in GSE39582. In addition, MCD predicted improved survival in stages II and III CRC patients receiving adjuvant chemotherapy (ACT). Multiple immune pathways were enriched in low MCD group while cytokines/chemokines promoting anti‐tumor immunity were highly expressed in such group. Furthermore, MCD was negatively correlated with CD8+ T cells infiltration. In conclusion, MCD was identified as an independent prognostic factor, as well as a potential biomarker for ACT benefit in stages II and III CRC. Better stratification of CRC prognosis could be achieved by building a MCD based nomogram. Moreover, immunoactivation in low MCD tumors may contributed to improved prognosis. Abstract : What's new? Mast cells are inflammatory mediators that tend to congregate in the tumor periphery. Little is known, however, about their function in the tumor microenvironment, or whether their density is associated with prognosis. Here, in colorectal cancer (CRC) patients, low tumor‐infiltrating mast cell density (MCD) was associated with increased overall survival, with MCD identified as an independent prognostic indicator. MCD was also found to predict survival among stage II and III CRC patients on adjuvant chemotherapy. Furthermore, low mast cell infiltration was associated with a more intense immune response, which may contribute to prolonged survival in low MCD patients.